Performance Improvement of TDOA-Based Speaker Localization in Joint Noisy and Reverberant Conditions. (24th January 2011) - Abutalebi Abutalebi, Hamid Reza Hamid Reza; Momenzadeh Momenzadeh, Hossein Hossein
Abstract : TDOA- (time difference of arrival-) based algorithms are common methods for speech source localization. The generalized cross correlation (GCC) method is the most important approach for estimating TDOA between microphone pairs. The performance of this method significantly degrades in the presence of noise and reverberation. This paper addresses the problem of 3D localization in joint noisy and reverberant conditions and a single-speaker scenario. We first propose a modification to make the GCC-PHAse transform (GCC-PHAT) method robust against environment noise. Then, we use an iterative technique that employs location estimation to improve TDOAs accuracy. Extensive experiments on both simulated and real (practical) data (in a single-source scenario) show the capability of the proposed methods to significantly improve TDOA accuracy and, consequently, source location estimates.